Effect of cholesterol re-supplementation and atorvastatin on plaque composition in the thoracic aorta of New Zealand white rabbits - Bonaterra, Gabriel; Bender, Katharina; Metz, Jürgen (BMC cardiovascular disorders, 2020)
Effects of re-supplementation of a cholesterol-enriched diet (CEDrs) on size, cholesterol content and morphology of already existing plaques are not known to date.